Notes for the improvement of sports management in Cuba: the case of baseball - Silvia Odriozola Guitart; Alejandro Rodríguez Martínez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2020)
The Cuban revolutionary government has made important efforts for the development of sports, what makes the country to show remarkable results. However, in the last years, it is observed a deterioration of many of these performances, which should be studied and faced, in the light of the current conditions. The particular case of baseball is a clear example, so the research aimed to identify those actions that can contribute to the improvement of sport management, especially at the base level. A diagnosis of the situation was made, based on the analysis of data from official sources and the results of a survey to relatives of children practicing baseball (category 7-8 years old) who participated in the provincial championship of Havana (2019 edition), processed with the SPSS program (version 22). The benefits of sports practice in the formation of human beings, associated with improvements in physical and mental health, disease prevention, formation of individual and collective values, were systematized. As for the practice of sports in Cuba, its most recent deterioration is due, among other factors, to the lack of attention to the basic level and the insufficient resources to which it has access. Hence, the need to use management forms with higher levels of decentralization, as well as to diversify the sources of financing, with a growing participation of the multiple actors that today make up Cuban society.